Exploring of Expressive Art Therapy in Counselling: A Recent Systematic Review - Siti NurulHida Abdul Rahman; Mohd Izwan Mahmud; Ku Suhaila Ku Johari (Qubahan Academic Journal)
Objectives: This systematic review aims to identify what themes are found in the study of expressive art therapy and counselling, and to identify and analyse the variety of therapeutic research methods and intervention settings to understand how these factors contribute to effective mental health care and therapeutic practise worldwide. Sometimes meeting the complex emotional needs of clients can require more work than typical counselling strategies. This encourages us to explore how EAT can improve therapeutic outcomes for people struggling with a range of mental health conditions. Design: A thorough and systematic review of the literature, including studies, research and applications of expressive arts therapy in counselling, was conducted using the PRISMA framework. Data source: Advanced techniques and targeted keywords were used to search SCOPUS and the Web of Science database. Following a mixed methods analysis of the resulting primary dataset (n = 20), three overarching themes were identified. Methods of review: The database used by the researcher was from 2020-2023. Based on this search, 20 articles met the specified criteria. Results: The initial conclusions of the study indicate that expressive arts therapy can promote the ongoing exploration and integration of creative and therapeutic approaches into mental health care, demonstrating a methodological approach to understanding and treating adult mental health through broader medical and academic methods.